Cardiovascular Disease Risk Factors among Migrant Seasonal Agricultural Workers: Comparison with Local Residents - Gulsum Ozturk Emiral; Muhammed Fatih Onsuz; Ozkan Ozay; Burhanettin İsikli; Selma Metintas (Tehran University of Medical Sciences, 2021)
Background: Seasonal agricultural workers group is one of the most disadvantageous groups of working life in Turkey same as many other countries. We aimed to determine the status of cardiovascular disease risk factors among migrant seasonal agricultural workers (MSAW) and to compare obtained data with local residents. Methods: This study cross-sectional study was conducted among MSAW in Eskisehir, Turkey and closest town residents in 2015 during agricultural season. These 455 MSAW were living in camps composed of 20 or more tents. Local residents sample composed of 532 local residents were reached at their houses by using random sampling method with data acquired from health organization records. Both groups were subjected to same questionnaire. Results: The prevalence of overweight/obesity among MSAW women was 40.5%, hypertension 19.9%, diabetes 4.9% and hypercholesterolemia 6.5%. These prevalences were 68.0%, 38.6%, 13.9% and 20.8% respectively among local residents. The prevalence of smoking risk among local residents was 1.5 times more than MSAW. In addition, the prevalence of overweight/obese risk was 4 times more; hypertension risk 1.8 times more, diabetes risk 3.8 times more and hypercholesterolemia risk 2.7 times more among local residents than MSAW (P<0.05). Conclusion: The prevalence of cardiovascular disease risk factors of MSAW was lower than local residents in the study groups. Even though health risks that MSAW faced were more linked with environment and life conditions, cardiovascular disease risk factors should not be ignored. Health services should be guided by considering obstacles that MSAW experienced in accessing health services.